Utilization of Bokashi Fertilizer from Restaurant Liquid Waste on Physical Parameters of Water Quality - Ek Putra Toyibin Sianipar; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Akuakultur SEBATIN, 2024)
The research it was conducted on June to July 2022 at the Aquaculture Environmental Quality Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This study aims to determine the effect of applying bokashi fertilizer from restaurant wastewater with different doses on the physical parameters of water quality. The method used was an experiment of Completely Randomized Design with one factor, four treatments, and three replications. The treatment used P0 = no application of bokashi fertilizer, P1 = 0.5 mL/L of bokashi fertilizer, P2 = 1 mL/L of bokashi fertilizer, P3 = 1.5 mL/L of bokashi fertilizer. Parameters observed were total suspended solid (TSS), total dissolved solid (TDS), temperature, pH and water color change. The results of this study indicate that the application of bokashi fertilizer with different doses has an effect on the physical parameters of water quality. The best treatment in this study was the P3 treatment (giving 1.5 ml/L of bokashi fertilizer). with the result of total suspended solid (TSS) 32,66 mg/L, total disolved solid (TDS), temperature 27-28oC, pH 6.9-7 and greenish brown water.